269 INJURY PREVENTION AWARENESS IN "TWEENS " AND COMPARISON OF TWO EDUCATIONAL FORUMS TO IMPROVE AWARENESS. (1st January 2006) - Chang, T.; Nichols, M.; King, W. D.; Monroe, K.
Abstract : Background: "Tweens, " children between the ages of 8 and 12 years old (sometimes called the forgotten years), are often seen in emergency departments (ED) for injury-related reasons. We sought to determine injury prevention awareness in this group and then to compare two educational interventions designed to improve awareness. Methods: Children between 8 and 12 years were recruited from our pediatric ED (both patients and siblings). On enrollment, patients completed a standardized pretest. They were then randomized to receive either a video of a series of vignettes or a written cartoon-like sheet both with injury prevention principles in car, bike, and fire safety. Following the intervention, a post-test along with a 2- to 4-week phone follow-up (FU) post-test were given. Tests were 15 questions (10 knowledge and 5 behavioral). Data were entered into Epistat and scores were compared using Student's t-test statistics. Results: A total of 87 children were enrolled with mean age of 10. Test scores improved after either intervention: #1 (video), 47% of participants improved their score; #2 (sheet), 68% improvement (t = 3.71, p < .01, 95% CI 29.2, 22.8). Those completing 2- to 4-week FU were similar to those who could not be reached for FU in pretest scores (t = 1.49, p = .14, 95% CI 1.2, 8.4). Two- to 4-week FU scores were significantly better than pretest scores, suggesting retention of information (t = 4.7, p < .001; 95% CI 4.1, 6.5). Interventions 1 and 2 FU post-test scores were not significantly different (t = 0.44, p = 0.66), 95% CI of the mean differences (26.5, 4.2). Pretest behavior questions: 89.7% appropriately sit in the back seat (post-test, 100% knew a person should be > 12 years old to sit in the front). Eighty-six percent reported having a bicycle (only 30% of those had a helmet—increased to 80% on 2- to 4-week FU). On pretest, only 18.4% reported wearing a helmet (100% stated yes on the 2- to 4-week FU test (81.6% increase, z = 8.41, p < .001, 95% CI 0.63, 1.00). Conclusion: Children between 8 and 12 respond well to either video or cartoon sheet and in this study showed improvement in test scores and retention of knowledge using either method. Emergency departments can be effective sites for education.